Perceived Shared Condemnation Intensifies Punitive Moral Emotions - Naoki Konishi (Nature Portfolio, 2017)
Abstract Punishment facilitates large-scale cooperation among humans, but how punishers, who incur an extra cost of punishment, can successfully compete with non-punishers, who free-ride on the punisher’s policing, poses an evolutionary puzzle. One answer is by coordinating punishment to minimise its cost. Notice, however, that in order to effectively coordinate their punishment, potential punishers must know in advance whether others would also be willing to punish a particular norm violator. Such knowledge might hinder coordination by tempting potential punishers to free-ride on other punishers. Previous research suggests that moral emotions, such as moral outrage and moral disgust, serve as a commitment device and drive people to carry out the costly act of punishment. Accordingly, we tested whether the perception of socially shared condemnation (i.e., knowledge that others also condemn a particular violator) would amplify moral outrage and moral disgust, and diminish empathy for the violator. Study 1 (scenario-based study) revealed that perceived shared condemnation was correlated positively with moral outrage and moral disgust, and negatively with empathy. Study 2 experimentally demonstrated that information indicating that others also condemn a particular norm violation amplified moral outrage. Lastly, Study 3 (autobiographical recall study) confirmed the external validity of the finding.